PXR pharmacogenetics: Association of haplotypes with hepatic CYP3A4 and ABCB1 messenger RNA expression and doxorubicin clearance in Asian breast cancer patients - Sandanaraj, E. (2016)
10.1158/1078-0432.CCR-08-0411